Frédéric Chopin: Einblicke in Unterricht und Umfeld. Die Briefe seiner Lieblingsschülerin Friederike Müller, Paris 1839-1845 - Goebl-Streicher, Uta (Munchen Salzburg Katzbichler, 2018)
Friederike Müller, a pianist from Vienna, travels in 1839 to Paris with her aunt and becomes élève de prédilection, one of the select students, of Frédéric Chopin. She studied with Chopin over the years 1839 – 1845. In a dense but very readable correspondence she reports back to two aunts in Vienna about her experience in Paris.The uniqueness of this document lies in the fact that Friederike reports weekly, and even in the heat of the moment, on her lessons and conversations with Chopin as well as on her encounters and activities in Paris. The letters, which are written in a mix of German and French, also provide an interesting insight in the exchanges between the Paris and Vienna musical scenes and how they compare in the eyes of this witty and observant young woman.Friederike gave her first public concert in Vienna in 1841. In 1841, the composer dedicated his Allegro de Concert opus 46 to her. Her destiny became very much intertwined with the history of the Streicher family; in 1849 she married Johann Baptist Streicher, son of Nannette and Andreas Streicher and then head of the Streicher piano building enterprise, who was recently widowed from his first wife Auguste.
Keywords: Chopin, Frédéric -- 1810-1849; Müller, Friederike -- 1816-1895; Pianist; Music education; Correspondence